The prevalence of HIV, HBV and HCV among Filipino blood donors and overseas work visa applicants - Yumiko Yanase; Takashi Ohida; Yoshitaka Kaneita; Dorothy May D Agdamag; Prisca Susan A Leaño; Christopher J Gill (The World Health Organization, 2007)
OBJECTIVE: Our aim was to estimate the prevalence of HIV, HBV and HCV among the general population of the Philippines using data sources outside of the limited existing active surveillance network. METHODS: We analysed aggregate HIV, HBV and HCV test results for hospital-based blood donors (BDs) and overseas Filipino worker candidates (OFWCs) that had been reported from licensed laboratories to the National STD/AIDS Cooperative Central Laboratory in Manila between 2002 and 2004. FINDINGS: From over 144 000 blood-screening results, the HIV prevalence was 0.006% in BDs and 0.001% in OFWCs; that of HBV was 4.2% in both groups; and that of HCV was 0.3% in BDs and 0.9% in OFWCs. Males were at increased risk of both HBV and HCV; among OFWCs, younger women were at increased risk. Laboratories that tested sequentially but stopped testing after the first positive result were far less likely to detect HCV, indicating that sequential testing protocols may underestimate HCV and HIV prevalence. OFWCs were at low risk of HIV, and the risk of testing positive for these viruses was not increased among OFWCs applying for a repeated work visa, compared with first time-applicants. CONCLUSION: Based on these data, we conclude that HIV is rare in the Philippines. In contrast with prior reports, we found no evidence that OFWCs constitute a high-risk group for HIV. Further research is needed to understand why younger women are at increased risk of acquiring HBV.